The patrimonial values of Santa Marina's Neighborhood Unit at Callao from the look of its residents and neighbors - Mechato Lara, Fiorella (2020)
Heritage conservation is carried out when its heritage actors work together and dialogue; there is no heritage if its main actors do not recognize the heritage value of the object that is why promoting heritage education in them and identifying the potential of the object hand in hand with the population is the key to its conservation. Under a social approach, the research aims to track heritage values, based on the classification of Dr. Cristina Nieto (Polytechnic University of Valencia, Spain), in the Santa Marina Neighborhood Unit of Callao from the opinions and perceptions of its direct actors: local residents, students, specialists and experts, and municipal institutions. Through instruments like the use of surveys, interviews, focus group sessions, and analysis sheets, patrimonial values were identified and weighted, whose results of the study revealed a recognition of values differentiated by social context but strong in a common dimension.